Preparation, characterization, and antibacterial application of cross-linked nanoparticles composite films - Yuxin Zhao; Guanglong Yao; Kaimian Li; Jianqiu Ye; Jian Chen; Jie Zhang (Food Chemistry: X, 2025)
This study aimed to prepare a composite film by blending cross-linked tapioca starch (CLTS) with sodium alginate (SA), silver nanoparticles (AgNPs), and ZnO nanoparticles (ZnOs). The effects of SA, AgNPs, and ZnOs at different concentrations (1–3 wt%) on the mechanical properties, optical properties, thermal stability, and antibacterial activity of cross-linked starch films were also investigated. The structures of the films were examined by Fourier transform infrared spectroscopy and X-ray diffraction. The results showed that the cross-linked starch, SA, AgNPs, and ZnOs had good biocompatibility and interactions, and the AgNPs and ZnOs had synergistic effects. ESEM also revealed that the polymer and nanofiller had good compatibility. The Young's modulus and tensile strength values of the CLTS/SA/AgNP/ZnO film increased from 351.64 MPa to 1879 MPa and from 13.77 MPa to 53.76 MPa, respectively, with increasing concentration of nano-ZnO particles. The decrease in elongation at break from 48.15 % to 24.60 % indicated a certain increase in rigidity and a decrease in flexibility. The ultraviolet barrier and thermal stability of the CLTS/SA/AgNP/ZnO film effectively improved, and the antibacterial activity increased; the antibacterial effect of the CLTS/SA/AgNP/ZnO film was better than that of Streptococcus aureus. The study revealed that the CLTS/SA/AgNP/ZnO composite film represented a packaging material with superior performance.